Pengaruh Media Word Search Puzzle terhadap Penguasaan Kosakata Bahasa Inggris Siswa Kelas IV MIS Nurul Hidayah - Salsabila Syifa Simbolon; Dody Feliks P. Ambarita; Eva Betty Simanjuntak; Robenhart Tamba; Apiek Gandamana (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study aims to determine the effect of the use of Word Search Puzzle media on English vocabulary mastery in grade IV students at MIS Nurul Hidayah Medan for the 2024/2025 academic year. Vocabulary mastery is an important aspect of learning English, as it is the basis for language skills such as reading, writing, speaking, and listening. In an effort to improve students' vocabulary skills, innovative, interesting, and interactive learning media is needed. One of the media used in this study is Word Search Puzzle, which is a game to find words in a letter box that can stimulate students' interest in learning and make it easier for them to recognize and remember new vocabulary. This study uses an experimental method with a One-Group Pretest-Posttest Design. The sample in this study is all fourth grade students of MIS Nurul Hidayah Medan, which totals 19 people. The research instrument was in the form of a multiple-choice test of 20 questions that measured students' English vocabulary mastery before and after treatment. The data was analyzed using the Paired Sample T-Test statistical test with the help of SPSS software. The results of the study showed a significant increase in the average score of students, from 55.26 in the pretest to 82.36 in the posttest. The hypothesis test showed a significance value of 0.000 (sig < 0.05), which means that Ho was rejected and Ha was accepted. Thus, it can be concluded that the use of Word Search Puzzle media has a significant influence on improving the English vocabulary mastery of grade IV students. These findings indicate that game-based learning media can be an effective strategy in English learning at the elementary school level.